1996
DOI: 10.1016/0304-3770(96)01027-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between waves, bank erosion and emergent vegetation: an experimental study in a wave tank

Abstract: Emergent vegetation development, wave extinction and soil erosion are strongly interrelated processes in exposed riparian zones. The above-ground parts of the vegetation reduce wave energy, while the below-ground parts strengthen the soil. On the other hand, vegetation development may be restricted as a result of wave stress. Interactions between waves, soil erosion, and emergent vegetation were studied during three consecutive years. Two helophyte species, Phrugmites australis (Cav.) Trin. ex Steudel and S&pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 16 publications
3
78
1
3
Order By: Relevance
“…13 Idealized relationships between beach geomorphology, ecological processes, and aquatic macroinvertebrates along sandy beaches (modified from Defeo and McLachlan 2005). Beach types are arranged from highly reflective to highly dissipative Fig. 14 Effects of Phragmites australis on wave attenuation and bank erosion in an experimental wave tank (Coops et al 1996). Waves approach from the right mineralization of wrack can be an important source of nutrients to nearshore microbes and phytoplankton (Malm et al 2004), as well as terrestrial microbes and vegetation.…”
Section: Accumulation and Processing Of Organic Mattermentioning
confidence: 99%
“…13 Idealized relationships between beach geomorphology, ecological processes, and aquatic macroinvertebrates along sandy beaches (modified from Defeo and McLachlan 2005). Beach types are arranged from highly reflective to highly dissipative Fig. 14 Effects of Phragmites australis on wave attenuation and bank erosion in an experimental wave tank (Coops et al 1996). Waves approach from the right mineralization of wrack can be an important source of nutrients to nearshore microbes and phytoplankton (Malm et al 2004), as well as terrestrial microbes and vegetation.…”
Section: Accumulation and Processing Of Organic Mattermentioning
confidence: 99%
“…The wave damping effects by common reed (Phragmites australis) has been investigated together with another emergent species (Scripus lacustris) in a tank experiment by Coops et al (1996) to analyze the potential for erosion protection from ship-induced waves at river banks. They showed that Phragmites australis reduced the wave height most effectively and this reed was also most capable to withstand the wave energy, while Scripus lacustris was damaged.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the Mediterranean, leaf litter commonly gets washed up on beaches, with up to 2 m of vertical accumulation, significantly reducing wave impact and erosion caused by waves and currents (Simeone and De Falco 2012). However, it remains unclear whether (i) flow and turbulence fields are always modified in a way that reduces erosion and/or enhances deposition and (ii) there are particular species, assemblages of species, stem, leaf and stand configurations and/or areal extents needed to sustain or attenuate hydrodynamic forcing (Coops et al 1996). In addition, further study is needed to document and quantify the complex response of the coastal ecosystem when leaf litter is removed.…”
Section: Examples Of Knowledge Gapsmentioning
confidence: 99%